Determine the Frequency of Blood Pressure Control among Hypertensive Patients and its Relationship with Diabetes Mellitus - Faisal Rahman, Maria Shireen, Imran Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypertension plays an important role in the development of secondary comorbidity in the patients. It is also noted that it also plays a role in the onset of diabetes among the patients. Objective: To evaluate the blood pressure control among hypertensive patients and its relationship with diabetes mellitus. Study Design: Cross-sectional study Place and Duration of Study: Department of Medicine, Social Security Teaching Hospital, Ferozpur Road Lahore from 1stMarch 2021 to 31stAugust 2021. Methodology: Two hundred and twenty seven patients with hypertension between 16-60 years of age of either gender were enrolled. Two readings of blood pressure of the patient was measured in supine position from brachial artery 20 minutes apart by the researcher himself and control of blood pressure was noted. Patients were assessed for having diabetes mellitus. Results: The mean age was 38.19±8.93 years and 117 (51%) were males and 110 (49%) were females. Forty four (19.4%) cases were having good blood pressure control. Eighty (35%) cases were having the diabetes mellitus. There were 20 (25%) cases who have diabetes and blood pressure control while 24 (16.3%) cases did not have diabetes but have blood pressure control with non-significant difference. Conclusion: Majority of patients had poor blood pressure control and there was a statistically non-significant relationship between diabetes mellitus and blood pressure control among hypertensive.